Lost to follow up from chronic care services during COVID-19 from health facilities, in Northwest Ethiopia - Belay, Daniel Gashaneh; Adugna, Asmamaw (Frontiers in Epidemiology, 2022)
Introduction: COVID-19 pandemic and the actions taken in response to it have significantly altered individual life’s especially those who have a chronic disease. The pandemic affected the processes of routine comprehensive care for, patients due to a disrupted care delivery system. Moreover, chronic diseases are immunosuppressing cases, making patients more vulnerable to infection such as the COVID-19 pandemic. These patients with the COVID-19 are more severely ill and less likely to be cured. Due to this, having a COVID-19 pandemic exacerbates the rate of loss to follow-up (LTFU) from chronic disease care. Therefore this study aimed to assess the mean difference of loss to follow up among HIV/AIDS, diabetes mellitus (DM), and hypertension patients during the pre-Covid-19 and Covid-19 period at health facilities in Northwest Ethiopia. Methods: An institution-based secondary data analysis of Gondar city extracted from central repository data of the ministry of health from October 2020 to Jun 2021 was done. Excel data were transformed to STATA 14 for analysis. Independent t-test was done to compare mean difference analysis of lost to follow up and new initiation of treatment among HIV/AIDS, DM, and Hypertension patients during pre-Covid-19 and Covid-19 period at facilities in Northwest Ethiopia. Variables with a mean difference p<0.005 with a 95% confidence interval were used to declare the significant level. Result: There was a significantly higher mean difference in the number of patients of LTFU from Anti-Retroviral Therapy (ART) during Covid-19 as compared to the pre-Covid-19 period [μd =17.85, 95%CI: 3.25, 32.95]. There was also a significant mean difference [μd =17.31, 95%CI: 8.35, 26.97] of patients LTFU from antihypertensive treatment during the Covid-19 period as compared to the pre-Covid-19 period. Conclusion: There was a significantly higher mean difference in the number of patients of LTFU from Anti-Retroviral Therapy (ART) and antihypertensive treatment during Covid-19 as compared to the pre-Covid-19 period. Therefore the Mistry of Health Ethiopia (MOH) should be revised and modify the chronic disease follow-up guideline and prepare a convenient follow-up method for the ongoing COVID-19 pandemic in Ethiopia.